Evaluation of anti-inflammatory properties of neutral lipids, glycolipids, and phospholipids from Oncorhynchus mykiss eggs in LPS-stimulated macrophages - Weerawan Rod-In; Ha Jun Lee; Sang-min Lee; Seok Kyu Jung; Woo Jung Park (Journal of Functional Foods)
The current study evaluated the anti-inflammatory activity of fractionized lipids obtained from Oncorhynchus mykiss eggs, including neutral lipids (OM-NL), glycolipids (OM-GL), and phospholipids (OM-PL). The fatty acid (FA) content of OM-NL and OM-GL revealed that PUFAs constitute a predominant portion of total FAs, accounting for 41.80 % and 40.96 %, respectively. However, OM-PL showed a higher content of MUFAs, which comprised 42.52 % of the total FAs. The fractionized lipids reduced the dose-dependency production of NO and iNOS expression in LPS-induced RAW264.7 cells. Subsequently, they reduced the transcript levels of TNF-α, IL-1β, and IL-6, and produced TGF-β and IL-10 expression, by inhibiting the phosphorylation of proteins involved in inflammatory responses within NF-κB and MAPK pathways. All lipids reduced the levels of PGE2, LTB4, and EETs by suppressing COX-1, COX-2, 5-LOX, and CYP4A11 proteins, which are involved in eicosanoid synthesis. Thus, our findings demonstrate that the fractionized lipids isolated from O. mykiss eggs have potential anti-inflammatory activity.